Correction and Parameter Calculation of Gas Logging and Geochemical Logging Interference in Shale Oil Reservoirs under Oil-Based Drilling Fluid Conditions - ZHENG Shanshan; SUN Jianmeng; YANG Dong; ZHANG Hengrong; CHENG Jiajie; WANG Meng (Cejing jishu, 2025)
During the process of oil and gas exploration, logging data is of great significance for the interpretation and evaluation of reservoirs. However, when oil-based drilling fluids are used in the drilling operations of complex wells, due to the large amount of petroleum and its derivatives contained in the oil-based drilling fluids, the data of gas logging and geochemical pyrolysis logging will be distorted, affecting the accurate identification and evaluation of reservoirs. This paper proposes a correction approach for the gas logging and geochemical pyrolysis logging data of shale oil reservoirs in Block X affected by oil-based drilling fluids. This paper takes into account the dual influences of environmental factors and oil-based drilling fluids on gas logging data, and based on the multi-component gasoline ratio calculation model, a more suitable multi-component volumetric gasoline ratio calculation model for Block X is proposed. For the geochemical pyrolysis logging data, this paper comprehensively analyzes the core pyrolysis experimental data of four wells, namely X-1, X-4, X-5 and X-8. By combining with conventional logging curves, a geochemical parameter calculation model is established to correct the influence of oil-based drilling fluids. The results show that the average coincidence rate between the calculated values and the experimental values reaches 91%. This study provides an effective method for the fine evaluation of shale oil reservoirs under the condition of oil - based drilling fluid, helps to improve the reliability of reservoir identification and evaluation, and is of great significance for the application of logging data in the exploration and development of shale oil.